A colorimetric/luminescent benzene compound sensor based on a bis(σ-acetylide) platinum(ii) complex: enhancing selectivity and reversibility through dual-recognition sites strategy1. Issue 80 (2nd September 2015) - Ni, Jun; Kang, Jia-Jia; Wang, Hui-Hui; Gai, Xu-Qiao; Zhang, Xiao-Xin; Jia, Ting; Xu, Liang; Pan, Yu-Zhen; Zhang, Jian-Jun
<x xml:space="preserve">Abstract</x> A concurrent, selective, naked-eye perceivable, sensitive, reversible, reproducible, and easy to use sensor for detecting vapors of benzene compounds has been developed.